Difference content of calcium in suffy pure goat milk and cow milk: a preliminary study/ Nunshaimah Salleh ... [et al.] - Salleh, Nunshaimah; Fadzil, Adibatul Husna; Zulkifli, Norsakina Zurina; Ali, Rosliza; Yaacob, Yanti; Mohmad Tahirudin, Nordiana Suhada (2023)
The purpose of this study is to compare the calcium content of goat milk and cow milk in order to determine the ideal milk for pregnant women. Both goat milk and cow milk are dissolved in nitric acid to ensure that the milk completely dissolves and calcium ions are released from the organic matrix. The technique employed in this study for quantifying calcium content in milk samples was Flame Atomic Absorption Spectroscopy (FAAS). The findings of the investigation indicate that goat's milk has a higher calcium content compared to cow's milk, hence positioning goat's milk as a more favourable option for expectant mothers.